DEVELOPMENT AND EVALUATION FOR EXTRUDED CHARACTERISTICS AND SENSORY ACCEPTABILITY OF EXTRUDED PRODUCTS WITH COMPOSITE FLOURS OF CORN AND SORGHUM - Y. LENIN KUMAR, E. SHARATH and (The Journal of Research, PJTSAU, 2017)
The extrusion cooking process is high temperature short time(HTST) process in which moist, soft grain is fed into the extruder where the desired temperature and pressure are obtained over the required period of residence time. For cooking of the product generally external heat is not supplied, heat for cooking is achieved through shear and friction in extruder. Extrusion cooking is used worldwide for the production of expanded snack foods, modified starches ready- to- eat cereals, baby foods, pasta and pet foods. (Toft, 1979). This technology has many distinct advantages viz., versatility, low cost, better product quality and no process effluents. Extrusion is accomplished by single screw and twin screw extruders. Extrusion cooking not only enhances the acceptability of the product by improving its appearance, taste and texture but also inactivates anti-nutritional factors such as trypsin inhibitor and urease activity etc. in legumes (Phillips, 1989).